Spanish seamen : inter-departmental correspondence (copy) - Carthy, A. E.
025a-0030-001 A.E. CARTHY. INTERNATIONAL. Mr H.V. TEWSON. 26th July 1940. SPANISH SEAMEN. The following is the response to the appeal. National Union of Seamen................ £40. Transport General Workers' Union...... £280. National Union of Railwaymen............ £500. 31/7/40 Navigators £20 5/8/40 Coal Trimmers £2/10/- NUDAW 40 292/946/25a/30